2014
DOI: 10.1007/s12039-013-0547-y
|View full text |Cite
|
Sign up to set email alerts
|

Signal amplification of dopamine using lanthanum hexacyanoferrate-modified electrode

Abstract: A sensitive and selective electrochemical sensor has been developed using an electroactive polynuclear lanthanum hexacyanoferrate (LaHCF) complex with counter alkali cation (Na +) deposited on the glassy carbon (GC) electrode (GC/LaHCF). The GC/LaHCF-modified electrode is found to be an excellent transducer in mediating the oxidation of neurotransmitter molecule such as dopamine (DA) at physiological pH 7.2. Interestingly, the GC/LaHCF-modified electrode amplifies a 50-fold enhancement in the oxidation of DA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The MHCF electrocatalytic effects were confirmed for H 2 O 2 , 1,4,10 NO 11 and some easily oxidizable species as ascorbic acid, 2,8 dopamine, 2,6 glucose, 9 sulfite. 5,7 The preparation of hexacyanoferrate films with ruthenium also has been reported.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The MHCF electrocatalytic effects were confirmed for H 2 O 2 , 1,4,10 NO 11 and some easily oxidizable species as ascorbic acid, 2,8 dopamine, 2,6 glucose, 9 sulfite. 5,7 The preparation of hexacyanoferrate films with ruthenium also has been reported.…”
Section: Introductionmentioning
confidence: 79%
“…Various metals have been used to prepare MH-CF-modified electrodes by chemical 4 or electrochemical 2,[5][6][7][8][9][10][11] methods. Data show that most of the modified electrodes were prepared via electrochemical deposition techniques owing to its low cost, low time consuming and well-defined structure forming ability by controlling the time, cycle number and nature of the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous efforts were carried out using various nanomaterials such as polymers, 7-9 metal nanoparticles, 10-15 core@shell nanostructures, 16,17 alloys, 18,19 two-dimensional layered materials, [20][21][22] carbon based [23][24][25][26] and metal/metal oxide nanocomposites. [27][28][29][30][31][32][33][34][35][36] Yin et al, reported a three-dimensional MoS 2 nanosheet for simultaneous detection of DA, UA and AA. 37 The peak separation for AA-DA, DA-UA and AA-UA were found to be 208.3 mV, 128.0 mV and 336.3 mV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the overwhelming activity on metal hexacyanoferrate, rare earth metal-HCFs have also been widely used in electrochemical sensor applications. [16][17][18][19][20] To date, several rare earth metal-HCFs such as dysprosium, 21,22 samarium, 23,24 and lanthanum HCF, 25 respectively, have been reported for preparation and characterization. Nonetheless, rare earth metal-HCFs have fascinating morphologies such as ower and christmas tree-like CeHCF, 26 diamond-like NdHCF, 27 LaHCF, 28 and parabola-like HoHCF.…”
Section: Introductionmentioning
confidence: 99%